Web-Based College Student Assignment File Collection Application Using Google Drive API - Khairi Ibnutama; Hendryan Winata; Masyuni Hutasuhut (The IJICS (International Journal of Informatics and Computer Science), 2019)
The use of internet media, especially cloud storage as a practical solution in information and communication should be able to be applied in academics, especially in the scope of teaching and learning. By using cloud storage as a communication medium, especially in sending data in the form of assignments files can facilitate lecturers and students in carrying out one of the mandatory activities in lectures, namely the collection of assignments. The main problem that often occurs is the storage capacity provided by hosting services is very limited, so storing large amounts of files will require large costs as well. Google Drive provides an API driven file storage service that makes it easy for users to create applications that can communicate and interact with 15 GB free storage services. The free service is expected to facilitate teaching and learning activities in lectures, especially in the collection of student assignments